Java for dummies quick reference - Lowe, Doug 1959- (For dummies, 2012)
This guide arms you with must-have Java commands, tips, syntax, and more to get the job done. You'll find clear and concise solutions instead of lengthy tutorials, so you can keep moving-- |c Source other than Library of Congress.